Efficacy and Safety of Bempedoic Acid in Patients With Hypercholesterolemia: Systematic Review and Meta‐Analysis of Randomized Controlled Trials. Issue 15 (4th August 2020) - Di Minno, Alessandro; Lupoli, Roberta; Calcaterra, Ilenia; Poggio, Paolo; Forte, Francesco; Spadarella, Gaia; Ambrosino, Pasquale; Iannuzzo, Gabriella; Di Minno, Matteo Nicola Dario
Abstract : Background: Bempedoic acid (BA) is a novel lipid‐lowering drug. We performed a systematic review and meta‐analysis on efficacy and safety of BA compared with standard treatment in patients with hypercholesterolemia. Methods and Results: Studies were systematically searched in the PubMed, Web of Science, Scopus, and EMBASE databases. Efficacy outcome was represented by percentage changes (mean difference [MD] with pertinent 95% CIs) in total cholesterol, low‐density lipoprotein cholesterol, triglycerides, high‐density lipoprotein cholesterol, apolipoprotein B, non–high‐density lipoprotein cholesterol, and hs‐CRP (high‐sensitivity C‐reactive protein) in BA patients and controls. Seven studies were included (2767 BA‐treated patients and 1469 controls), showing a more significant reduction in low‐density lipoprotein cholesterol (MD, −17.5%; 95% CI, −22.9% to −12.0%), total cholesterol (MD, −10.9%; 95% CI, −13.3% to −8.5%), non–high‐density lipoprotein cholesterol (MD, −12.3%; 95% CI, −15.3% to −9.20%), apolipoprotein B (MD, −10.6%; 95% CI, −13.2% to −8.02%), and hs‐CRP (MD, −13.2%; 95% CI, −16.7% to −9.79%) in BA‐treated patients compared with controls. Results were confirmed when separately analyzing studies on patients with high cardiovascular risk, studies on statin‐intolerant patients, and studies on patients with hypercholesterolemia on maximally tolerated lipid‐lowering therapy. BA‐treated subjects reported a higher rate of treatment discontinuation caused by adverse effects, of gout flare, and of increase in uric acid compared with controls. On the other hand, BA‐treated patients showed a lower incidence of new‐onset diabetes mellitus than controls. Conclusions: BA is associated with a significant reduction in low‐density lipoprotein cholesterol, total cholesterol, non–high‐density lipoprotein cholesterol, apolipoprotein B, and hs‐CRP compared with standard treatment. Documented efficacy is accompanied by an acceptable safety profile.